2021
DOI: 10.1080/21655979.2021.2010315
|View full text |Cite
|
Sign up to set email alerts
|

Hsp22 ameliorates lipopolysaccharide-induced myocardial injury by inhibiting inflammation, oxidative stress, and apoptosis

Abstract: Sepsis-induced myocardial dysfunction (SIMD) is ubiquitous in septic shock patients and is associated with high morbidity and mortality rates. Heat shock protein 22 (Hsp22), which belongs to the small HSP family of proteins, is involved in several biological functions. However, the function of Hsp22 in lipopolysaccharide (LPS)-induced myocardial injury is not yet established. This study was aimed at investigating the underlying mechanistic aspects of Hsp22 in myocardial injury induced by LPS. In this study, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
(36 reference statements)
1
30
0
Order By: Relevance
“…Experiments were carried out in this study to determine if the exogenous Ang-(1–7) pretreatment could regulate RAAS, and the outcome of these experiments showed that Ang-(1–7) effectively inhibits the biological function of Ang II, thereby alleviating SIC. Excessive inflammatory responses and oxidative stress can aggravate cardiomyocyte apoptosis and promote the occurrence and development of SIC [ 61 , 62 ]. We observed that the LPS stimulation resulted in an excessive inflammatory response, elevated ROS production, and increased cardiomyocyte apoptosis in the in vivo and in vitro SIC models.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were carried out in this study to determine if the exogenous Ang-(1–7) pretreatment could regulate RAAS, and the outcome of these experiments showed that Ang-(1–7) effectively inhibits the biological function of Ang II, thereby alleviating SIC. Excessive inflammatory responses and oxidative stress can aggravate cardiomyocyte apoptosis and promote the occurrence and development of SIC [ 61 , 62 ]. We observed that the LPS stimulation resulted in an excessive inflammatory response, elevated ROS production, and increased cardiomyocyte apoptosis in the in vivo and in vitro SIC models.…”
Section: Discussionmentioning
confidence: 99%
“…ROS promote the release of pro‐inflammatory mediators. The process in turn produces more ROS 5,6,9 . The vicious cycle has a detrimental effect on tissues by mediating mitochondrial disturbance, aggravating cellular damage and eventually leading to chronic diseases 5,9 …”
Section: Discussionmentioning
confidence: 99%
“…Under stress conditions, this pathway mediates mitochondrial homeostasis, oxidative stress and apoptosis, and has cytoprotective activity, thereby accelerating the recovery of nerve function [ 61 ]. In addition, other studies have reported that Hsp22 inhibits oxidative stress-induced hippocampal neuronal cell death by regulating mitochondrial pathway and that Hsp22 improves lipopolysaccharide induced myocardial injury [ 62 , 63 ]. In contrast to existing studies, our study is the first to shows that Hsp22 targets the NLRP3/caspase-1/IL-1β pathway to improve LPS-induced cognitive impairment, that Hsp22 preconditioning reduces the LPS-induced inflammatory response and cell apoptosis and improves learning and memory impairment in mice.…”
Section: Discussionmentioning
confidence: 99%